GREEN FACTOR OF ECONOMIC GROWTH IN UZBEKISTAN (PROBLEMS AND PROSPECTS) (American Journal of Business Management, Economics and Banking, 2023)
The article discusses the features, problems and prospects of the green factor of economic growth in Uzbekistan, analyzes international experience in the transition to a green economy, and also describes the main directions of development of the green economy in the Republic of Uzbekistan.